SISTEM INFORMASI MANAJEMEN NAZWA WEDDING ORGANIZER BERBASIS WEB - Restika Putri Andini (Indragiri Islamic University, 2021)
ABSTRACT Until now, Nazwa Wedding Organizer does not have a special application that is used as a means of wedding services in the data management process, where the process is still using a ledger, starting from recording, searching for tenant data, ordering, paying and making reports. This method has several drawbacks, namely long transactions, errors can occur, tenants who are far from the wedding organizer services must come directly to the location to make orders and payments. Therefore we need a software development process in the form of a wedding organizer nazwa management information system which aims as a means for tenants who want to make transactions with wedding organizer services both when they want to make orders and payments, and as a means for wedding services to input. , search for tenant data and report generation. The processes carried out are data collection in the form of observations, interviews and literature studies, system analysis, system design or design, system implementation and system testing or testing. The system development method used is the waterfall method, while the analysis method used is the pieces method which can be a reference in building a web-based wedding organizer nazwa management information system. The modeling system used is a web-based UML (Unified Modeling Language) modeling with PHP (Hypertext Preprocessor) programming language and MYSQL database. The Nazwa wedding organizer management information system that has been built functions according to User needs, namely in inputting tenant data, searching for tenant data, managing order data, managing payment data, and managing booking reports. With the Nazwa wedding organizer management information system, it is hoped that it can be useful as a means for the wedding party and the tenant in conducting transactions so that time becomes more effective. Keywords : Web-Based Management Information System, Wedding Organizer Application, Nazwa Wedding Organizer Tembilahan.